Reviews Left and Right: The Link Between Reviewers’ Political Ideology and Online Review Language - Graf-Vlachy, Lorenz; Goyal, Tarun; Ouardi, Yannick; König, Andreas (Business & Information Systems Engineering, 2020)
Online reviews, i.e., evaluations of products and services posted on websites, are ubiquitous. Prior research observed substantial variance in the language of such online reviews and linked it to downstream consequences like perceived helpfulness. However, the understanding of why the language of reviews varies is limited. This is problematic because it might have vital implications for the design of IT systems and user interactions. To improve the understanding of online review language, the paper proposes that consumers’ personality, as reflected in their political ideology, is a predictor of such online review language. Specifically, it is hypothesized that reviewers’ political ideology as measured by degree of conservatism on a liberal–conservative spectrum is negatively related to review depth (the number of words and the number of arguments in a review), cognitively complex language in reviews, diversity of arguments, and positive valence in language. Support for these hypotheses is obtained through the analysis of a unique dataset that links a sample of online reviews to reviewers’ political ideology as inferred from their online news consumption recorded in clickstream data.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Online consumer reviews; Political ideology; Review language; Reviewer personality

The politics of piracy: political ideology and the usage of pirated online media - Graf-Vlachy, Lorenz; Goyal, Tarun; Ouardi, Yannick; Koenig, Andreas (Information Technology & Management, 2021)
There is a lack of clarity in information systems research on which factors lead people to use or not use technologies of varying degrees of perceived legality. To address this gap, we use arguments from the information systems and political ideology literatures to theorize on the influence of individuals’ political ideologies on online media piracy. Specifically, we hypothesize that individuals with a more conservative ideology, and thus lower openness to experience and higher conscientiousness, generally engage in less online media piracy. We further hypothesize that this effect is stronger for online piracy technology that is legally ambiguous. Using clickstream data from 3873 individuals in the U.S., we find that this effect in fact exists only for online media piracy technologies that are perceived as legally ambiguous. Specifically, more conservative individuals, who typically have lower ambiguity intolerance, use (legal but ambiguously perceived) pirated streaming websites less, while there is no difference for the (clearly illegal) use of pirated file sharing websites.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Ambiguity intolerance; File sharing; Legal issues; Online streaming; Piracy; Political ideology